Stainless steel aluminum-based composite material and selective laser printing-casting preparation method thereof

The stainless steel frame added to rare earth oxides is printed through selective laser printing technology, and the inside is filled with boron carbide aluminum alloy, which solves the problem of combining stainless steel and aluminum alloys in neutron shielding performance, and achieves lightweight and efficient neutron shielding Performance, suitable for multi-field applications.

CN119237760APending Publication Date: 2025-01-03TAIYUAN UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411228185.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-03
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing technology is difficult to achieve the dual advantages of stainless steel and aluminum alloy through a single preparation method. Combined with its excellent neutron shielding performance, it is used for the preparation of functional/structural parts. The selected laser additive manufacturing technology has problems such as slow printing speed and high cost. .

Method used

Selective laser printing technology is used to print rare earth oxides with circular hollow array structure and add stainless steel frames, and fill the stainless steel hollow frame with boron carbide added aluminum alloy through casting method to prepare stainless steel aluminum-based composite materials, combining stainless steel and aluminum-based Advantages of boron carbide materials.

Benefits of technology

It significantly reduces the weight of functional/structural parts, and has excellent neutron shielding performance, adapts to shielding protection needs in different fields, has short process, simple equipment and high efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119237760A_ABST
    Figure CN119237760A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of non-ferrous metal preparation, and relates to a stainless steel aluminum-based composite material and a selective laser printing-casting preparation method thereof. According to the method, a framework with a circular hollow array structure and a rare earth oxide added stainless steel structure is printed through a selective laser additive manufacturing technology, the stainless steel hollow framework is filled with aluminum alloy added with boron carbide through a casting method, and the weight of the prepared iron-aluminum-based composite material can be remarkably reduced; the neutron shielding material has the advantages of light weight, high strength, excellent corrosion resistance, excellent irradiation resistance and good neutron shielding performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nonferrous metal preparation, and relates to a stainless steel aluminum-based composite material and a preparation method thereof by selective laser printing-casting. Background Art

[0002] Stainless steel has excellent corrosion resistance, radiation resistance and superior mechanical properties, and has been widely used as a structural / functional material in the nuclear power field. Boron (B), rare earth and its oxides, etc., which have good neutron absorption properties, are added to stainless steel to prepare boron steel or rare earth steel, which can be used as neutron shielding materials.

[0003] Compared with stainless steel, aluminum alloy has low density and light weight, which plays an important role in reducing the weight of functional / structural parts. Boron, boron carbide or rare earth and its oxides are added to aluminum alloy to prepare boron aluminum alloy, aluminum-based boron carbide, etc., which have been used in the field of nuclear shielding. Combining the characteristics of stainless steel and aluminum-based nuclear shielding materials, an iron-aluminum-based composite shielding material with excellent neutron shielding performance and dual advantages of stainless steel and aluminum alloy is prepared, which has broad potential application prospects. However, due to the differences in physical and chemical properties between stainless steel and aluminum alloy, it is difficult to achieve using traditional single preparation methods.

[0004] Selective laser additive manufacturing technology has the characteristics of short component trial production cycle, flexible material composition design, and complex and diverse structures. It can realize the preparation of multi-structure / multi-type composite materials, but the printing speed of selective laser additive manufacturing components is slow and the cost is high. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a stainless steel aluminum-based composite material by selective laser printing-casting. The method uses selective laser additive manufacturing technology to print a skeleton of a rare earth oxide-added stainless steel structure with a circular hollow array structure, and fills the interior of the stainless steel hollow skeleton with an aluminum alloy added with boron carbide by a casting method. The obtained iron-aluminum-based composite material can significantly reduce the weight of functional / structural parts, and at the same time combines the advantages of stainless steel and aluminum-based boron carbide materials to have excellent neutron shielding performance to meet the needs of shielding protection in different fields.

[0006] The technical solution adopted by the present invention to solve its technical problem is:

[0007] A method for preparing a stainless steel aluminum-based composite material by selective laser printing-casting, the method comprising the following steps:

[0008] S1. Preparation of Y2O3 / 316L mixed powder

[0009] Yttrium oxide (Y2O3) and stainless steel (316L) powders are mixed to make the mass percentage of yttrium oxide in the mixed powder be 0.6-1.5wt.%, and then placed in a drying oven for drying at a drying temperature of 80°C ± 5°C for a drying time of 30min-40min;

[0010] Place the dried powder in a ball mill at a speed of 300r / min, a mixing time of 60min, a ball-to-material ratio of 2-2.5:1, and mix well for use;

[0011] Selective laser additive manufacturing printing of S2, Y2O3 / 316L-based composites

[0012] The Y2O3 / 316L mixed powder obtained after ball milling was placed in a drying oven, preheated to 80±5℃, and dried for 3.5h. After drying, it was naturally cooled to room temperature, and nitrogen protection was introduced during the drying process;

[0013] The Y2O3 / 316L composite material was printed by selective laser additive manufacturing using the dried Y2O3 / 316L mixed powder. The printing adopted a checkerboard scanning strategy.

[0014] After printing is completed, the test piece is taken out, and the printed Y2O3 / 316L hollow block is cleaned using a high-speed argon gas flow at a pressure of 0.5MPa-0.8MPa; the inner surface of the hollow structure of the Y2O3 / 316L hollow block is polished using an abrasive flow process to improve the surface roughness of the hollow structure inside the block;

[0015] S3, B4C / 6061 aluminum alloy melt preparation

[0016] Weighing a 6061 aluminum alloy ingot and placing it in a crucible, placing the crucible in a heating furnace for melting, and protecting it with inert gas argon during the melting process to reduce oxidation of the aluminum alloy and clean the surface impurities of the molten aluminum alloy melt;

[0017] Adding boron carbide (B4C) particles into the molten aluminum alloy melt one by one, stirring continuously during the adding process, the stirring speed is 50r / min-100r / min, and ultrasonic waves are applied during the stirring process, the ultrasonic wave frequency is 20kHz-60kHz, to ensure that the B4C particles are evenly distributed in the aluminum alloy melt, and the added content of the B4C particles is between 5wt.% and 10wt.%, based on the total weight of the B4C / 6061 aluminum alloy melt as 100%;

[0018] S4. Die casting of stainless steel and aluminum matrix composite materials

[0019] The cylindrical specimen of the Y2O3 / 316L-based composite material with a hollow array structure prepared by printing is placed inside an H13 steel mold, and the preheating temperature is 150°C-200°C; the molten B4C / 6061 aluminum alloy melt is cast into each hollow array of the cylindrical specimen, and the pouring temperature is 680°C-720°C; the die-casting test machine is turned on to die-cast the stainless steel aluminum-based composite material; the pressure is maintained for 10min-20min during the die-casting process, and after the die-casting is completed, the pressure is released, the mold is opened, and the die-cast stainless steel aluminum-based composite material is taken out;

[0020] S5, after grinding and sanding treatment, the product is obtained.

[0021] The stainless steel aluminum-based composite material of the present invention is formed by die casting. Compared with the selective laser additive manufacturing technology, the casting method has the advantages of short process, simple equipment and high efficiency.

[0022] Preferably, the mass percentage of yttrium oxide in the mixed powder in S1 is 1 wt.%.

[0023] Preferably, the Y2O3 / 316L-based composite material described in S2 is prepared as a skeleton structure in a selective laser additive manufacturing printer. The selective laser additive manufacturing printer includes a chamber and a molding cavity located below it. A scanning galvanometer and a laser are installed above the chamber. The laser generates a laser beam, which irradiates the molding cavity. Push rod two is connected below the molding cavity. A feeding cylinder is arranged on the right side of the molding cavity. A push rod one is connected below the feeding cylinder. A powder scraper is arranged at the upper right of the feeding cylinder; a powder recovery cavity is arranged on the left side of the molding cavity; a control cabinet one is arranged on the right side of the selective laser additive manufacturing printer, and an operation panel one and a display screen one are arranged on the control cabinet one.

[0024] Preferably, in S2, the interior of the Y2O3 / 316L-based composite material is a circular hollow array structure, the diameter of the hollow circle is 5mm-8mm, the center distance between the centers of the circles is 12mm-15mm, the size of the printed component is 100mm-200mm×100mm-200mm×50mm-100mm, and the axis of the hollow array circular structure is parallel to the printing construction direction.

[0025] Preferably, in S2, the process parameters of the selective laser additive manufacturing printing are: laser power of 200W, laser scanning speed of 1000mm / s-1200mm / s, scanning spacing of 0.12mm-0.15mm, and single layer powder thickness of 30μm-40μm;

[0026] During the printing process, high-purity argon gas with a purity of 99.9% was filled in. The oxygen content in the selective laser additive manufacturing printing chamber was less than 0.1%. 316L stainless steel was selected as the substrate material, and the substrate was preheated to 80℃±5℃.

[0027] Preferably, in S2, the fluid abrasive in the abrasive flow process uses SiC with a mass fraction of 30-35wt.% and a particle size of 100-150 mesh as abrasive particles, a styrene-butadiene rubber carrier, and an appropriate amount of softener;

[0028] Place the printed Y2O3 / 316L hollow block specimen on an abrasive flow polisher with an abrasive flow rate of 35mm / s-45mm / s and 5-6 reciprocating times. After the surface finishing is completed, take out the specimen for use.

[0029] Preferably, the abrasive flow polishing machine comprises a supporting platform, a hydraulic cylinder 1, a hydraulic cylinder 2, a material cylinder 1 and a material cylinder 2. The supporting platform is supported by a left leg 1 and a right leg 1. A track is installed on the supporting platform. A supporting frame 1, a supporting frame 2, a supporting frame 3 and a supporting frame 4 are installed on the track. Hydraulic cylinder 1 and hydraulic cylinder 2 are installed on the supporting frame 4 and the supporting frame 3 respectively. Hydraulic cylinder 1 and hydraulic cylinder 2 are connected to plunger 1 and plunger 2 respectively. Abrasive is filled in material cylinder 1 and material cylinder 2, and the abrasive is loaded through a filling port arranged on material cylinder 1. Fastening ring 1 and fastening ring 2 are located on both sides of the workpiece for fixing the workpiece.

[0030] The fastening ring 2 is connected to the material cylinder 2 through the connecting bolt 1, nut 1, connecting bolt 4, nut 4; the fastening ring 1 is connected to the material cylinder 1 through the connecting bolt 2, nut 2, connecting bolt 3, nut 3; the material cylinder 2 is equipped with an exhaust hole; the hydraulic cylinder 1 and the hydraulic cylinder are connected to the control cabinet 2 through the connecting wire, connecting wire, connecting wire 3, and the control cabinet 2 is provided with an operation screen.

[0031] Preferably, in S4, press leg one and press leg two are installed below the die-casting testing machine, a workbench is installed above press leg one and press leg two, a mold is placed above the workbench, a workpiece is placed inside the mold, a resistance heating wire is installed outside the mold, a boron carbide aluminum alloy melt is installed on the top of the workpiece, a pressure head is located directly above the boron carbide aluminum alloy melt, the pressure head is connected to the connecting platform through a connecting head, a support platform is arranged above the connecting platform, an oil cylinder is arranged above the support platform, the oil cylinder is connected to the oil tank through an oil return pipe and an oil inlet pipe; slide column one and slide column two are installed between the connecting platform and the workbench; an oil return pressure gauge and an oil inlet pressure gauge are installed on the upper left part of the oil tank.

[0032] A stainless steel aluminum-based composite material made according to the preparation method of the present invention.

[0033] Preferably, the main body of the stainless steel aluminum-based composite material is a Y2O3 / 316L-based composite material with a hollow array structure, which is cylindrical, and the interior of the hollow array is filled with B4C / 6061 aluminum alloy material; the 316L matrix has a cellular substructure, and high-density spherical Y2O3 nanoparticles are evenly distributed on the cell wall.

[0034] The beneficial effects of the present invention are as follows: the present invention aims at the special application of stainless steel and aluminum alloy, adopts rare earth oxides and boron carbide as neutron absorbers and reinforcements, designs a circular hollow skeleton structure inside the stainless steel matrix, adopts a selective laser additive manufacturing method to realize the printing preparation of the stainless steel hollow skeleton structure added with rare earth oxides, and adopts a casting method to cast the molten metal with boron carbide particles added inside the aluminum alloy into the stainless steel hollow skeleton, so as to prepare a stainless steel aluminum-based composite material to meet the needs of shielding protection in different fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 It is a schematic diagram of the structure of the stainless steel aluminum matrix composite material and the scanning microstructure of the Y2O3 / 316L skeleton and the B4C / 6061 aluminum alloy under high magnification;

[0036] Figure 2 It is a schematic diagram of the Y2O3 / 316L framework structure formation state;

[0037] Figure 3 It is a schematic diagram of the polishing of the inner surface of the Y2O3 / 316L framework;

[0038] Figure 4 It is a schematic diagram of die-casting of stainless steel aluminum matrix composite materials;

[0039] The list of reference numerals is as follows: 1. stainless steel base frame, 2. hollow structure, 3. push rod 1, 4. feeding cylinder, 5. powder scraper, 6. chamber, 7. scanning galvanometer, 8. laser, 9. laser beam, 10. molding chamber, 11. push rod 2, 12. powder recovery chamber, 13. control cabinet 1, 14. operation panel 1, 15. display screen 1, 17. left leg 1, 18. support platform, 19. support frame 1, 20. Connecting bolt 1, 21, nut 1, 22, track, 23, nut 2, 24, connecting bolt 2, 25, support frame 2, 26, right leg 1, 27, support frame 3, 28, connecting wire 1, 29, control cabinet 2, 30, operation screen, 31, connecting wire 2, 32, hydraulic cylinder 1, 33, plunger 1, 34, material cylinder 1, 35, stuffing port, 36, connecting bolt 3, 37, nut 3, 38, fastening ring 1, 3 9. Workpiece, 40. Nut 4, 41. Fastening ring 2, 42. Connecting bolt 4, 43. Cylinder 2, 44. Exhaust hole, 45. Plunger 2, 46. Hydraulic cylinder 2, 47. Support frame 4, 48. Connecting wire 3, 49. Press leg 1, 50. Control cabinet 3, 51. Display 3, 52. Indicator light, 53. Power switch button, 54. Temperature control button, 55. Speed ​​control button, 56. Fuel tank, 5 7. Oil return pipe, 58. Oil inlet pipe, 59. Oil return pressure gauge, 60. Oil inlet pressure gauge, 61. Connecting line four, 62. Workpiece, 63. Connecting head, 64. Sliding column one, 65. Connecting table, 66. Oil cylinder, 67. Support table, 68. Sliding column two, 69. Press head, 70. Resistance heating wire, 71. Mold, 72. Boron carbide aluminum alloy melt, 73. Workbench, 74. Press leg two, 75. Connecting line five. DETAILED DESCRIPTION

[0040] The technical solution of the present invention is further described in detail below through specific embodiments. It should be understood that the implementation of the present invention is not limited to the following embodiments, and any form of modification and / or change made to the present invention will fall within the protection scope of the present invention.

[0041] In the present invention, unless otherwise specified, all parts and percentages are by weight, and the equipment and raw materials used can be purchased from the market or are commonly used in the art. The methods in the following embodiments are all conventional methods in the art unless otherwise specified.

[0042] The reagents used in the following examples, unless otherwise specified, can be purchased from conventional biochemical reagent stores.

[0043] Material preparation: measured in grams and millimeters

[0044] Aluminum alloy ingot: 6061Al 1 piece,

[0045] 316L stainless steel powder particle size 1-3μm 3000g±0.1g,

[0046] Boron carbide powder (B4C) particle size 15-75μm 1000g±0.1g,

[0047] Yttrium oxide powder (Y2O3) particle size 30nm-100nm 500g±0.1g,

[0048] Graphite paper: C 2 pieces 90mm×2mm×90mm,

[0049] Sandpaper: 400 mesh, 2 sheets, 300mm×0.5mm×200mm.

[0050] Selective laser additive manufacturing printer, model FF-M140-H, Dalian Meiguangsu Technology Co., Ltd.

[0051] Example:

[0052] A method for preparing a stainless steel aluminum-based composite material and a selective laser printing-casting method thereof, the specific steps are:

[0053] 1. Preparation of Y2O3 / 316L mixed powder

[0054] Yttrium oxide (Y2O3) and stainless steel (316L) powders were mixed so that the mass percentage of yttrium oxide in the mixed powder was 1%, and the mixed powder was placed in a drying oven for drying at a drying temperature of 80°C and a drying time of 30 minutes.

[0055] Place the dried powder in a ball mill with a speed of 300r / min, a mixing time of 60min, a ball-to-material ratio of 2:1, and set aside for use after mixing.

[0056] 2. Selective laser additive manufacturing printing of Y2O3 / 316L-based composites

[0057] The Y2O3 / 316L-based composite material has a circular hollow array structure inside, the hollow circle has a diameter of 5 mm, the center distance between the centers of the circles is 12 mm, the printed component size is 100 mm×100 mm×50 mm, and the axis of the hollow array circular structure is parallel to the printing construction direction;

[0058] The Y2O3 / 316L-based composite material is used as a skeleton structure in a selective laser additive manufacturing printer (schematic diagram as shown in Figure 2The present invention is prepared on a surface of the molding cavity 10 (as shown in the figure), specifically comprising a chamber 6 and a molding cavity 10 located below the chamber 6, a scanning galvanometer 7 and a laser 8 are installed above the chamber 6, the laser 8 generates a laser beam 9, and the laser beam 9 irradiates the molding cavity 10, a push rod 11 is connected below the molding cavity 10, a feeding cylinder 4 is arranged on the right side of the molding cavity 10, a push rod 3 is connected below the feeding cylinder 4, and a powder scraper 5 is arranged on the upper right side of the feeding cylinder 4; a powder recovery chamber 12 is arranged on the left side of the molding cavity 10; a control cabinet 13 is arranged on the right side of the selected area laser additive manufacturing printer, and an operation panel 14 and a display screen 15 are arranged on the control cabinet 13.

[0059] The steps for selective laser additive manufacturing printing are as follows:

[0060] ① Place the Y2O3 / 316L mixed powder obtained after ball milling in a drying oven, preheat the drying temperature to 80±5℃, and dry for 3.5h. After drying, cool it naturally to room temperature. Nitrogen protection is introduced during the drying process;

[0061] ②Put the dried Y2O3 / 316L mixed powder into the feeding cylinder; install and fix the 316L stainless steel substrate, and preheat the substrate to 80℃; after closing the hatch, continuously introduce high-purity argon gas with a purity of 99.9% during the printing process, and control the oxygen content in the chamber to be less than 0.1%; slice the designed circular hollow array structure model, and use the checkerboard scanning strategy for printing. Set the process parameters as follows: laser power of 200W, laser scanning speed of 1000mm / s, scanning spacing of 0.12mm, single-layer powder thickness of 30μm, and import it into the printing equipment; print the Y2O3 / 316L-based composite material;

[0062] ③ After printing is completed, take out the specimen and clean the printed Y2O3 / 316L hollow block using a high-speed argon flow at a pressure of 0.5 MPa;

[0063] ④ The inner surface of the hollow structure of the Y2O3 / 316L hollow block is polished by an abrasive flow process to improve the surface roughness of the hollow structure inside the block.

[0064] The fluid abrasive uses SiC with a mass fraction of 30wt.% and a particle size of 100 mesh as abrasive particles, a styrene-butadiene rubber carrier, and an appropriate amount of softener.

[0065] The printed Y2O3 / 316L hollow block specimen was placed on an abrasive flow polishing machine with an abrasive flow rate of 35 mm / s and 5-6 reciprocating times. After the surface finishing was completed, the specimen was taken out for use.

[0066] The structural diagram of the abrasive flow polishing machine is as follows Figure 3As shown, the support platform 18 is supported by the left support leg 17 and the right support leg 1 26, and the support platform 18 is installed with a track 22, and the support frame 19, the support frame 25, the support frame 3 27 and the support frame 4 47 are installed on the track 22, and the hydraulic cylinder 1 32 and the hydraulic cylinder 2 46 are installed on the support frame 4 47 and the support frame 3 27 respectively, and the hydraulic cylinder 1 32 and the hydraulic cylinder 46 are connected with the plunger 1 33 and the plunger 2 45 respectively; the material cylinder 1 34 and the material cylinder 2 43 are filled with abrasives, and the abrasives are loaded through the filling port 35 set on the material cylinder 1 34; the fastening ring 1 38 and the fastening ring 2 41 are located on both sides of the workpiece 39 for fixing the workpiece 39,

[0067] The fastening ring 2 41 is connected to the material cylinder 2 43 through the connecting bolt 1 20, the nut 1 21, the connecting bolt 42, the nut 40 and the material cylinder 1 34; the fastening ring 1 38 is connected to the material cylinder 1 34 through the connecting bolt 24, the nut 23, the connecting bolt 36, the nut 37; the material cylinder 2 43 is provided with an exhaust hole 44; the hydraulic cylinder 1 32 and the hydraulic cylinder 46 are connected to the control cabinet 2 29 through the connecting line 28, the connecting line 31, the connecting line 3 48, and the control cabinet 2 29 is provided with an operating screen 30.

[0068] 3. Preparation of B4C / 6061 aluminum alloy melt

[0069] Weighing a 6061 aluminum alloy ingot and placing it in a crucible, placing the crucible in a heating furnace for melting, and protecting it with inert gas argon during the melting process to reduce oxidation of the aluminum alloy and clean the surface impurities of the molten aluminum alloy melt;

[0070] Boron carbide (B4C) particles are added gradually to the molten aluminum alloy melt, and stirring is continued during the adding process at a speed of 50 r / min. Ultrasonic waves are applied simultaneously during the stirring process at a frequency of 20 kHz to ensure that the B4C particles are evenly distributed in the aluminum alloy melt. The added content of the B4C particles is between 5wt.% and 10wt.%, based on the total weight of the B4C / 6061 aluminum alloy melt as 100%.

[0071] 4. Die casting of stainless steel and aluminum-based composite materials

[0072] A cylindrical specimen of the Y2O3 / 316L-based composite material with a hollow array structure prepared by printing is placed inside a H13 steel mold and preheated to a temperature of 150°C-200°C; the molten B4C / 6061 aluminum alloy is cast into each hollow array of the cylindrical specimen at a pouring temperature of 680°C-720°C; the die-casting testing machine is turned on to die-cast the stainless steel aluminum-based composite material; the pressure is maintained for 10 minutes during the die-casting process, and after the die-casting is completed, the pressure is released, the mold is opened, and the die-cast stainless steel aluminum-based composite material is taken out.

[0073] Die casting equipment is as follows Figure 4 The die-casting test machine shown in the figure has press leg 1 49 and press leg 2 74 installed below the die-casting test machine, a workbench 73 installed above the press leg 1 49 and press leg 2 74, a mold 71 placed above the workbench 73, a workpiece 62 placed inside the mold 71, a resistance heating wire 70 installed outside the mold 71, a boron carbide aluminum alloy melt 72 installed on the top of the workpiece 62, a pressure head 69 directly above the boron carbide aluminum alloy melt 72, the pressure head 69 is connected to the connecting platform 65 through the connecting head 63, and a support platform is arranged above the connecting platform 65 67, an oil cylinder 66 is arranged above the support platform 67, and the oil cylinder 66 is connected with the oil tank 56 through the return oil pipe 57 and the oil inlet pipe 58; a slide column 1 64 and a slide column 2 68 are installed between the connecting platform 65 and the working table 73; an oil return pressure gauge 59 and an oil inlet pressure gauge 60 are installed on the upper left part of the oil tank 56; the resistance heating wire 70 and the oil tank 56 are connected with the control cabinet 3 50 through the connecting line 4 61 and the connecting line 5 75, and the control cabinet 3 50 is provided with a display screen 3 51, an indicator light 52, a power switch button 53, a temperature control button 54 and a speed control button 55.

[0074] The main body of the stainless steel aluminum-based composite material is a Y2O3 / 316L-based composite material with a hollow array structure, which is cylindrical, and the interior of the hollow array is filled with B4C / 6061 aluminum alloy material. The Y2O3 / 316L skeleton structure of the stainless steel aluminum-based composite material and the schematic diagram of the scanning microstructure of the Y2O3 / 316L skeleton and B4C / 6061 aluminum alloy under high magnification are shown in the figure. Figure 1 The hollow pore diameter of the Y2O3 / 316L skeleton structure is 5mm, the center distance is 12mm, and it can be designed as needed. Figure 1 (1) is a schematic diagram of the scanning microstructure of the Y2O3 / 316L framework after polishing at high magnification. The 316L matrix presents a cellular substructure, and high-density spherical Y2O3 nanoparticles are evenly distributed in the cell wall; Figure 1 (2) is a schematic diagram of the scanning microstructure of the B4C / 6061 aluminum-based alloy surface under high magnification, and the B4C reinforcement particles are evenly distributed in the aluminum matrix.

[0075] 5. Grinding and sanding

[0076] The prepared stainless steel aluminum matrix composite material is placed on a steel flat plate, and the periphery and surface are polished with sandpaper to make it clean;

[0077] 6. Detection, analysis, and characterization

[0078] The morphology, color, chemical and physical properties, and mechanical properties of the prepared stainless steel aluminum matrix composite material are tested, analyzed, and characterized;

[0079] Microstructure analysis was performed using a scanning electron microscope;

[0080] Use a universal tensile tester to analyze tensile properties;

[0081] Conclusion: The prepared stainless steel aluminum matrix composite material has a skeleton structure of yttria added to stainless steel, and B4C / 6061 aluminum alloy is added inside the skeleton structure. It has the structural characteristics of structure / function in one, and has good neutron shielding performance, corrosion resistance and radiation resistance. The shielding components yttria, boron carbide, etc. are evenly distributed inside the matrix, and the various heterogeneous interfaces are well bonded, and have excellent mechanical properties.

[0082] 7. Storage

[0083] The prepared stainless steel aluminum-based composite material is packaged with soft materials and stored in a clean and dry environment. It must be protected from moisture, sunlight, acid, alkali and salt corrosion. The storage temperature is 20°C and the relative humidity is ≤10%.

[0084] In summary, the present invention adopts the selective laser additive manufacturing technology to print a skeleton of a rare earth oxide-added stainless steel structure with a circular hollow array structure, and fills the interior of the stainless steel hollow skeleton with an aluminum alloy added with boron carbide by a casting method. The obtained iron-aluminum-based composite material can significantly reduce the weight of functional / structural parts, and at the same time combines the advantages of stainless steel and aluminum-based boron carbide materials to have excellent neutron shielding performance, and has broad application prospects in medical protection, nuclear power military industry, electronic and electrical engineering and other fields.

[0085] In this specification, each embodiment is described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the embodiments can be referred to each other. For the device disclosed in the embodiment, since it corresponds to the method disclosed in the embodiment, the description is relatively simple, and the relevant parts can be referred to the method part.

[0086] The above is a detailed introduction to a stainless steel aluminum-based composite material and a preparation method of selective laser printing-casting provided by the present invention. Specific examples are used in this article to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, the present invention can also be improved and modified, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

Claims

1. A method for preparing a stainless steel aluminum-based composite material by selective laser printing-casting, characterized in that The method comprises the following steps: S1. Preparation of Y2O3 / 316L mixed powder Yttrium oxide (Y2O3) and stainless steel (316L) powders are mixed to make the mass percentage of yttrium oxide in the mixed powder be 0.6-1.5wt.%, and then placed in a drying oven for drying at a drying temperature of 80°C ± 5°C for a drying time of 30min-40min; Place the dried powder in a ball mill at a speed of 300r / min, a mixing time of 60min, a ball-to-material ratio of 2-2.5:1, and mix well for use; Selective laser additive manufacturing printing of S2, Y2O3 / 316L-based composites The Y2O3 / 316L mixed powder obtained after ball milling was placed in a drying oven, preheated to 80±5℃, and dried for 3.5h. After drying, it was naturally cooled to room temperature, and nitrogen protection was introduced during the drying process; The Y2O3 / 316L composite material was printed by selective laser additive manufacturing using the dried Y2O3 / 316L mixed powder. The printing adopted a checkerboard scanning strategy. After printing is completed, the test piece is taken out, and the printed Y2O3 / 316L hollow block is cleaned using a high-speed argon gas flow at a pressure of 0.5MPa-0.8MPa; the inner surface of the hollow structure of the Y2O3 / 316L hollow block is polished using an abrasive flow process to improve the surface roughness of the hollow structure inside the block; S3, B4C / 6061 aluminum alloy melt preparation Weighing a 6061 aluminum alloy ingot and placing it in a crucible, placing the crucible in a heating furnace for melting, and protecting it with inert gas argon during the melting process to reduce oxidation of the aluminum alloy and clean the surface impurities of the molten aluminum alloy melt; Adding boron carbide (B4C) particles into the molten aluminum alloy melt one by one, stirring continuously during the adding process, the stirring speed is 50r / min-100r / min, and ultrasonic waves are applied during the stirring process, the ultrasonic wave frequency is 20kHz-60kHz, to ensure that the B4C particles are evenly distributed in the aluminum alloy melt, and the added content of the B4C particles is between 5wt.% and 10wt.%, based on the total weight of the B4C / 6061 aluminum alloy melt as 100%; S4. Die casting of stainless steel and aluminum matrix composite materials The cylindrical specimen of the Y2O3 / 316L-based composite material with a hollow array structure prepared by printing is placed inside an H13 steel mold, the preheating temperature is 150°C-200°C, and the molten B4C / 6061 aluminum alloy melt is cast into each hollow array of the cylindrical specimen, and the pouring temperature is 680°C-720°C; the die-casting test machine is turned on to die-cast the stainless steel aluminum-based composite material; the pressure is maintained for 10min-20min during the die-casting process, and after the die-casting is completed, the pressure is released, the mold is opened, and the die-cast stainless steel aluminum-based composite material is taken out; S5, after grinding and sanding treatment, the product is obtained.

2. The preparation method according to claim 1, characterized in that: The Y2O3 / 316L-based composite material described in S2 is prepared as a skeleton structure in a selective laser additive manufacturing printer. The selective laser additive manufacturing printer includes a chamber (6) and a molding chamber (10) located below it. A scanning galvanometer (7) and a laser (8) are installed above the chamber. The laser (8) generates a laser beam (9), and the laser beam is irradiated on the molding chamber. A push rod 2 (11) is connected below the molding chamber. A feeding cylinder (4) is arranged on the right side of the molding chamber. A push rod 1 (3) is connected below the feeding cylinder (4). A powder scraper (5) is arranged on the upper right side of the feeding cylinder (4); and a powder recovery chamber (12) is arranged on the left side of the molding chamber.

3. The preparation method according to claim 1, characterized in that: In S2, the interior of the Y2O3 / 316L-based composite material is a circular hollow array structure, the diameter of the hollow circle is 5mm-8mm, the center distance between the centers of the circles is 12mm-15mm, the size of the printed component is 100mm-200mm×100mm-200mm×50mm-100mm, and the axis of the hollow array circular structure is parallel to the printing construction direction.

4. The preparation method according to claim 1, characterized in that: In S2, the process parameters of the selected area laser additive manufacturing printing are: laser power of 200W, laser scanning speed of 1000mm / s-1200mm / s, scanning spacing of 0.12mm-0.15mm, and single layer powder thickness of 30μm-40μm; During the printing process, high-purity argon gas with a purity of 99.9% was filled in. The oxygen content in the selective laser additive manufacturing printing chamber was less than 0.1%. 316L stainless steel was selected as the substrate material, and the substrate was preheated to 80℃±5℃.

5. The preparation method according to claim 1, characterized in that: In S2, the fluid abrasive in the abrasive flow process uses SiC with a mass fraction of 30-35wt.% and a particle size of 100-150 mesh as abrasive particles, a styrene-butadiene rubber carrier, and an appropriate amount of softener; Place the printed Y2O3 / 316L hollow block specimen on an abrasive flow polisher with an abrasive flow rate of 35mm / s-45mm / s and 5-6 reciprocating times. After the surface finishing is completed, take out the specimen for use.

6. The preparation method according to claim 5, characterized in that: The abrasive flow polishing machine comprises a support platform, a hydraulic cylinder 1, a hydraulic cylinder 2, a material cylinder 1 and a material cylinder 2. The support platform (18) is supported by a left support leg 1 (17) and a right support leg 1 (26). A track (22) is installed on the support platform. A support frame 1 (19), a support frame 2 (25), a support frame 3 (27) and a support frame 4 (47) are installed on the track. A hydraulic cylinder 1 (32) and a hydraulic cylinder 2 (46) are installed on the support frame 4 and the support frame 3 respectively. The hydraulic cylinder 1 and the hydraulic cylinder are connected to the plunger 1 and the plunger 2 (45) respectively. Abrasives are filled in the material cylinder 1 (34) and the material cylinder 2 (43). The abrasives are loaded into the material cylinder 1 through a filling port (35) arranged on the material cylinder 1. A fastening ring 1 (38) and a fastening ring 2 (41) are located on both sides of a workpiece (39) for fixing the workpiece.

7. The preparation method according to claim 1, characterized in that: In S4, a press leg 1 (49) and a press leg 2 (74) are installed below the die-casting test machine, a workbench (73) is installed above the press leg 1 and the press leg 2, a mold (71) is placed above the workbench, a workpiece (62) is placed inside the mold, a resistance heating wire (70) is installed outside the mold, a boron carbide aluminum alloy melt (72) is installed on the top of the workpiece, a pressure head (69) is located directly above the boron carbide aluminum alloy melt, the pressure head is connected to the connecting platform (65) through a connecting head (63), a support platform (67) is arranged above the connecting platform, an oil cylinder (66) is arranged above the support platform, and the oil cylinder is connected to the oil tank (56) through an oil return pipe (57) and an oil inlet pipe (58); a slide column 1 (64) and a slide column 2 (68) are installed between the connecting platform and the workbench; and an oil return pressure gauge (59) and an oil inlet pressure gauge (60) are installed on the upper left part of the oil tank (56).

8. A stainless steel aluminum-based composite material prepared according to the preparation method according to claim 1.

9. The stainless steel aluminum-based composite material according to claim 8, characterized in that: The main body of the stainless steel aluminum-based composite material is a Y2O3 / 316L-based composite material with a hollow array structure, which is cylindrical. The interior of the hollow array is filled with B4C / 6061 aluminum alloy material; the 316L matrix presents a cellular substructure, and high-density spherical Y2O3 nanoparticles are uniformly distributed on the cell wall.

Citation Information

Cited By

  • Composite metal structure and preparation method

    CN119457014A